2018
DOI: 10.2967/jnumed.117.203489
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Mesothelin-Specific Ligands for SPECT Imaging of Triple-Negative Breast Cancer

Abstract: Mesothelin is a cell-surface glycoprotein restricted to mesothelial cells overexpressed in several types of cancer, including triplenegative breast cancer not responding to trastuzumab or hormonebased therapies. Mesothelin-targeting therapies are currently being developed. However, the identification of patients potentially eligible for such a therapeutic strategy remains challenging. The objective of this study was to perform the radiolabeling and preclinical evaluation of 99m Tc-A1 and 99m Tc-C6, two antimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Our in vivo experiments showed that 99m Tc-A1 enabled the noninvasive visualization of AsPC-1-derived tumors by SPECT imaging at early time points. These results reinforce our study on triple-negative breast cancer, despite the lower 99m Tc-A1 uptake of PDAC mesothelin-positive tumors [9]. In addition to triple-negative breast cancer and PDAC, 99m Tc-A1 imaging represents a relevant option to visualize other aggressive cancers overexpressing mesothelin such as ovarian and lung cancers, for which the imaging modalities are mainly based on the use of conventional antibodies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our in vivo experiments showed that 99m Tc-A1 enabled the noninvasive visualization of AsPC-1-derived tumors by SPECT imaging at early time points. These results reinforce our study on triple-negative breast cancer, despite the lower 99m Tc-A1 uptake of PDAC mesothelin-positive tumors [9]. In addition to triple-negative breast cancer and PDAC, 99m Tc-A1 imaging represents a relevant option to visualize other aggressive cancers overexpressing mesothelin such as ovarian and lung cancers, for which the imaging modalities are mainly based on the use of conventional antibodies.…”
Section: Discussionsupporting
confidence: 85%
“…Nuclear imaging represents a highly sensitive and noninvasive imaging modality that could address this challenge. Indeed, we previously validated 99m Tc-A1, which is a single-domain antibody-derived imaging agent, as an efficient probe in accurately targeting mesothelin-expressing triple-negative breast cancer [9]. Herein, we evaluated the potential of 99m Tc-A1 as an imaging probe of mesothelin-expressing PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major application field for nanobody-based radiotracers is cancer imaging. Radiolabeled nanobodies targeting tumor biomarkers such as the epidermal growth factor receptor (EGFR), carcinoembryonic antigen (CEA), mesothelin, prostate-specific membrane antigen (PSMA), CD20, or HER2 showed high specific tumor uptake (ranging typically between 2 and 10% IA/g, depending on the expression level of the target) in preclinical tumor models as soon as 1 h after administration, with tumor-to-blood ratios of up to 10–30 (Figure 1B,C) [23,35,38,41,42,45,48,49,53,54,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Of particular interest is the anti-HER2 nanobody 2Rs15d that has been selected as a lead compound for clinical translation.…”
Section: Radiolabeled Nanobodies For Same-day High-contrast Nuclementioning
confidence: 99%
“…Hence, several molecules are currently in clinical phases to evaluate the therapeutic performance of its targeting in tumors expressing mesothelin [96]. Among companion markers, some monoclonal antibodies and nanobodies have been evaluated in clinical and in preclinical models of breast cancers [89][90][91]. Once available in clinical practice, such agents will allow selecting patients eligible to all these therapies.…”
Section: Other Imaging Agents Currently In Developmentmentioning
confidence: 99%